EL NINO MODOKI IMPACTS ON INDONESIA RAINFALL - TRISTANIA (NIM : 12809013), SONA
Modoki which is on Japanese literature has a meaning as "a similar but different thing" is used to designate El Nino event that occurred not as usual. The mechanism difference between El Nino Modoki and conventional El Nino caused the difference impact of those events. Researches about the impact of El Nino to the amount of rainfall in Indonesia have been considerably done, but the impact of El Nino Modoki to the amount of rainfall in Indonesia is still rarely studied, hence this topic is interesting to be studied. This research was conducted using rainfall data obtained from the Global Precipitation Climatology Centre (GPCC) and El Nino Modoki Index are processed using three methods, the calculation of changes in rainfall, relationship analysis using Pearson correlation, and analysis of lead/lag time by using cross-correlation. Analysis of changes in rainfall and Pearson correlation give results that changes in rainfall and the closest relationship between El Nino Modoki and rainfall in Indonesia occurred in the region with the greatest type of local rainfall and during the dry season (JJA). The changes in rainfall occurred is a decreasing of rainfall by over 30% of normal events. In other hand, the result of the correlation between EMI and rainfall in Indonesia shows high correlation around during 3 months before and after the peak of El Nino Modoki and the highest correlation is on the type of local rainfall.